Cadonilimab rechallenge in patients with recurrent or metastatic cervical cancer following prior PD-1/PD-L1 inhibitor failure: a retrospective multicenter study - Yu, Haijuan; Chen, Jian; Lin, Jie; Chen, Lijun; Zou, Jianping; Liu, Bin; Liu, Linying; Xie, Ning; Deng, Sufang; Zhou, Shengtao; Sun, Yang (Frontiers in Immunology, 2026)
PurposePatients with recurrent or metastatic cervical cancer (R/M CC) who progress after immunotherapy face limited treatment options. This study aimed to explore whether cadonilimab, a novel bispecific antibody targeting programmed cell death protein 1 (PD-1)/cytotoxic T-lymphocyte antigen-4 (CTLA-4), could effectively treat such patients following PD-1/programmed death-ligand 1 (PD-L1) inhibitor failure.MethodsA retrospective multicenter study was conducted on 29 patients with R/M CC who received cadonilimab treatment after immune checkpoint inhibitor (ICI) failure between August 2022 and April 2024. The study assessed the objective response rate (ORR), the disease control rate (DCR), the progression-free survival (PFS), the overall survival (OS), and the safety profiles. Given the small sample size and its retrospective nature, this study is fundamentally descriptive, and its findings should be interpreted as exploratory.ResultsAmong the 29 patients, the ORR was 24.1% (7/29) and the DCR was 55.2% (16/29). The median PFS was 5.8 months, while the median OS was 12.1 months. Subgroup analyses identified poorer prognoses for patients with liver metastasis, those with three or more prior treatment lines, and those receiving cadonilimab monotherapy. The most common grade 3 or higher adverse events (AEs) were anemia [8 (27.6%)], decreased white blood cell count [4 (13.8%)], and decreased neutrophil count [4 (13.8%)].ConclusionCadonilimab might offer a promising option with a manageable safety profile for patients with R/M CC who progress after ICI treatment. Further studies with larger sample sizes are needed to confirm these findings.